Pengaruh Persepsi Bauran Pemasaran Terhadap Kepuasan Pelanggan Di Percetakan Tiara Limboto Kabupaten Gorontalo - Elfis Mus Abdul (Gorontalo Management Research, 2018)
ELFIS MUS ABDUL, 2018. marketing hotchpotch perception influence towards customer satisfaction at Printing Office Tiara Limboto regency.This watchfulness aims to detect influence presepsi marketing hotchpotch towards customer satisfaction at Printing Office Tiara Limboto regency Gorontalo. Data that used in this watchfulness primary data that baseds on from admission filling kuisioner. Watchfulness population number 50 customers by using incedental method. Technics analysis that used to answer watchfulness problem and test hypothesis doubled regression analysis constructively software statistical package social science (spss) that is used to analyze data. Before do hypothesis test, done validity testing and reliabilitas instrument that continued pegujian regression analysis rules.This watchfulness finding (1) Found positive influence and significant Product towards customer satisfaction at Printing Office Tiara Limboto regency Gorontalo, (2) Found positive influence and significant Price towards customer satisfaction at printing office Tiara Limboto regency Gorontalo, (3) Found positive influence and significant Place towards customer satisfaction at Printing Office Tiara Limboto regency Gorontalo, (4) Found positive influence and significant Promotion towards customer satisfaction at Printing Office Tiara Limboto regency Gorontalo.Testing simultaneously attribute that product, price, place and promotion positive influential and significant towards customer satisfaction at printing office Tiara Limboto regency Gorontalo. Influential dominant variable towards customer satisfaction at Printing Office Tiara Limboto regency Gorontalo is Place.